Evaluation of palatability, protein and energi consumtion of adult lizard (Mabouya multifasciata) by feed them of with many diet variations - RONI RIDWAN; NAHROWI NAHROWI; Hj. LILY AMALIA SOFYAN (Society for Indonesian Biodiversity, 2001)
Lizard (Mabouya multifasciata), one of natural resources that spreads almost all Indonesian islands. The animals can potentially be used as a source of protein and medicine as well as a pet. The objectives of the research were therefore to investigate the preference of certain kind of diet, measure the protein and energy consumption, and also to observe the weight gain of the lizard. Seventy two lizards consisting of 36 females that each having weight of 29.7 + 2.6 grams and 36 male that having weight of 30.0 + 2.9 grams were used in this study. These lizards were captured from their wild nature around Bogor, Ciamis, Sumedang and Cianjur of West Java. Blockexperimental design was used, with 4 diet treatments and two grouping based on sex, (male and female). The diets were crickets, mealworm, red ant larva and artificial diet. Each tree lizards was put on 0.30m x 0.30m x 0.50m nets made from glass. Diets were given 3% dry matter of lizard body weight and water has given ad libitum. Parameter measured was dry matter consumption, protein consumption, energy consumption and body weight gain. ANOVA used for the data analysis, followed with Duncan range-test. The result showed that dry matter consumption of crickets, red ant larva and artificial diet was significantly (P<0.01) higher than mealworms. Consumption of crickets crude-protein was significantly (P<0.01) higher than mealworms, red ant larva and artificial diet. Mealworm crude-protein consumption was significantly (P<0.01) lower compared with both red ant larva and artificial diet. Crickets and red ant larva showed higher affect (P<0.01) on body weight gain thanartificial diet. However, there were no significant effect of all diet on consumption, brute energy and relatively metabolic energy. Grouping based on sex also did not show any significant affect to all parameters observed. It can be concluded that lizards prefer eating crickets, red ant larva and diet than mealworms.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKeywords: feeding variants, palatability, protein, energy consumption, lizard.